2012
DOI: 10.1097/shk.0b013e3182471795
|View full text |Cite
|
Sign up to set email alerts
|

Early Complementopathy After Multiple Injuries in Humans

Abstract: After severe tissue injury, innate immunity mounts a robust systemic inflammatory response. However, little is known about the immediate impact of multiple trauma on early complement function in humans. In the present study we hypothesized that multiple trauma results in immediate activation, consumption and dysfunction of the complement cascade and that the resulting severe “complementopathy” may be associated with morbidity and mortality. Therefore a prospective multicenter study with 25 healthy volunteers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
150
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(161 citation statements)
references
References 38 publications
5
150
1
Order By: Relevance
“…In particular, the serine protease system, composed of the kinin, coagulation and complement cascades, can detect DAMPs and PAMPs, become rapidly activated after trauma 18,19 and be further bolstered in acidic (for example, hypoxic) microenvironments 20 . Either directly or via such activated systems, DAMPs and PAMPs can transmit their signals to leukocytes through pattern-recognition receptors (PRRs) such as TLRs, NLRs, RAGE, purinergic receptors or complement receptors 11,12,21 .…”
Section: Protective and Harmful Innate Immune Responses To Traumamentioning
confidence: 99%
“…In particular, the serine protease system, composed of the kinin, coagulation and complement cascades, can detect DAMPs and PAMPs, become rapidly activated after trauma 18,19 and be further bolstered in acidic (for example, hypoxic) microenvironments 20 . Either directly or via such activated systems, DAMPs and PAMPs can transmit their signals to leukocytes through pattern-recognition receptors (PRRs) such as TLRs, NLRs, RAGE, purinergic receptors or complement receptors 11,12,21 .…”
Section: Protective and Harmful Innate Immune Responses To Traumamentioning
confidence: 99%
“…tudies of traumatic brain injury (TBI) in human and experimental models have identified the complement system as an early mediator of posttraumatic neuroinflammation and secondary neuronal damage, ultimately leading to behavioral, emotional, and cognitive problems (1)(2)(3)(4)(5)(6)(7)(8). Therefore, timely intervention to target activation of the complement system may be a promising therapy to reduce neuropathology and improve neurologic outcome in patients with TBI.…”
mentioning
confidence: 99%
“…traumatic brain injury | complement | therapy | CD59 | CRIg C ognitive, behavioral, and emotional sequelae of traumatic brain injury (TBI) are largely due to neuroaxonal damage secondary to the mechanical injury (1,2). Complement is an early determinant of posttraumatic neuroinflammation and secondary neuropathology (3)(4)(5)(6)(7); therefore, timely intervention to block complement activation may reduce neuroinflammation, neurodegeneration, and neurologic decline. Previous studies showed that complement inhibition protects in experimental TBI; however, most agents targeted the C3 convertase, the point of activation pathway convergence, resulting in broad inhibition of complement (8,9).…”
mentioning
confidence: 99%